Anticardiolipin antibodies in rheumatoid patients treated with etanercept or conventional combination therapy: direct and indirect evidence for a possible association with infections. Issue 4 (1st April 2002) - Ferraccioli, G; Mecchia, F; Di Poi, E; Fabris, M
Abstract : Objective: To assess the occurrence of anticardiolipin antibodies (ACA) (as well as of anti-DNA antibodies) in patients with rheumatoid arthritis treated with etanercept or combination therapy. Methods: Eight patients treated with etanercept 25 mg twice weekly were studied for a period of 85 weeks. A control group of 39 patients with rheumatoid arthritis undergoing combination treatment (methotrexate (MTX) + cyclosporin A or MTX + chloroquine) were studied for the same period of time. The occurrence of anticardiolipin antibodies (ACA-IgG) and anti-DNA was examined, together with the possible occurrence of infections due to bacteria capable of inducing B cell activation. Results: In 5/8 patients receiving etanercept an increase of ACA-IgG was seen, while anti-DNA became positive in 3/8 patients. A nasal or bronchial infection due to Staphylococcus aureus ( Staph aureus ) or a urinary tract infection due to E coli, occurred in all five cases. Antibiotic treatment produced a return to normal of ACA-IgG, and also of anti-DNA, in all cases except one. The infectious agent was eradicated in all subjects but one. In the control group Staph aureus was found in the nasal swab in 10/39 subjects; ACA-IgM (followed by ACA-IgG) appeared at the same time as infection occurred in 6/10, while no infection related to the increased ACA-IgM was recorded in the other four. Conclusions: Bacterial DNA, especially that enriched in CpG motifs, is a powerful immunostimulant that may, in some cases, lead to ACA or anti-DNA positivity, once tumour necrosis factor α is blocked. Eradication of the infections leads to a rapid decrease of ACA-IgG and of anti-DNA levels.